PENGARUH MODEL PEMBELAJARAN BERBASIS TEKNOLOGI DAN TEKNIK ASESMEN TERHADAP HASIL BELAJAR TERMODINAMIKA - Makahinda, Tineke (Jurnal Evaluasi Pendidikan, 2016)
The Purpose of this research is to find out the effect of technology based learning model and assessment technique toward thermodynamic achievement by controlling student’s intelligence. This research is an experimental research with factorial 2 x 2 design. The samples are taken by using cluster random sampling with total respondence of 80 students. The result of the research, after controlling students intelegence, shows that: (1) the students achievement of thermodynamic taught by the environmental use learning model is higher than that of the animation simulation learning model, (2) the students achievement of thermodynamic by project assessment is higher than the students achievement by portfolio assessment, (3) there is interactional effect between learning model based on technology and assessment technique toward thermodynamic achievement, (4) the students achievement of thermodynamic taught by the environmental use learning model by project assessment is higher than that of the animation simulation learning model by project assessment, and (5) the students achievement of thermodynamic taught by the environmental use learning model by project assessment is higher than that of the students achievement of thermodynamic taught by the environmental use learning model by portfolio assessment. Based on the findings of this study, it will be better if the thermodynamic lecture adopted environmental exploitation learning model with the use of project assessment technique.